Haphephobia as Reflected by the Main Character Kim Min Kyu in Yu Hyung Joong’s “I am not a Robot” Drama Series (2017) - Imaningtara, Icha; Widiyanti, Ana (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2023)
This research aims to analyze haphephobia represented in the main character of the drama series entittled I am not a Robot (2017). The are two formulations in this research. First, how are the symptoms of haphephobia reflected in Kim Min Kyu in “I am not a Robot” drama series (2017) and how does Kim Min Kyu overcome as the sufferer of haphephobia. The researchers use qualitative methods to describe and explain the data. The researchers collect data by watching movies and reading subtitles from the drama I am not a Robot. In this study the researcher used theory of Sigmund Freud. The results of the study that the researcher found many symptoms related to haphephobia such as being fear of human touch, and panic attack, body shaking or tremors, dizzy, nauseous, heartbeat pounding, fast or short breathing, and crying. The main character has three ways to overcome haphephobiareflected in the movie such as psychotherapy, administration drugs, relaxation technique.